Creating Cohesive Volunteer Groups: The Role of Group Identification in Volunteer Fire Services - Henderson, Alexander C.; Sowa, Jessica (Public administration quarterly, 2023)
Critical services are delivered to the public through collaborative or group activity, and building the skills to work effectively with others is arguably an essential core competency for those serving the public through nonprofit organizations. This article examines the question of how to foster effective groups when members of those groups are volunteers who engage in complex and dangerous work with low control over their job environments—volunteer firefighters. Using survey data from firefighters, we explore the question of how volunteers view their group experience— the degree to which they perceive cohesive groups through dimensions of affective, behavioral, and cognitive group identification — and what factors impact this group identification. Results indicate that transformational leadership impacts both affective and cognitive identification, while participation efficacy impacts behavioral and cognitive group identification. Extensive and collective group training experiences have a positive effect on all three types of identification. The article concludes with discussion and implications for nonprofit and volunteer management and how to harness these identification processes to build more cohesive volunteer groups.